2016
DOI: 10.5812/jjm.31338
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Viral Infections and Co-stimulatory Gene Polymorphisms in Kidney Transplant Outcomes

Abstract: BackgroundThe surveillance of kidney transplant patients depends on function of different immunologic markers like co-stimulatory molecules. These molecules may also be associated with post kidney transplant viral related outcomes.ObjectivesThe aim of this study was to investigate the possible associations between co-stimulatory molecule gene polymorphisms and viral infections in kidney transplant patients.Patients and MethodsIn total, 172 kidney transplant patients were included in this study. Single nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The significance of the association of LILRB1 SNPs with HCMV disease is that it may be useful as part of a collection of biomarkers used to determine the relative risk for patients after receiving a transplant and to guide prophylactic use of antivirals in these patients. Many studies have investigated genetic influences on the immune response to HCMV; the genes implicated in modulating the control of HCMV after transplantation include IL-28B, CCL8, several microRNA, CLTA4, TLR9, DC-SIGN, and, most relevant to NK cells, NKG2C and KIRs (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). Further studies with additional cohorts could be useful to pinpoint the SNPs with the best correlation and to explore the relationship to the sequence of UL18 within each patient.…”
Section: Genotyping Of Transplant Patientsmentioning
confidence: 99%
“…The significance of the association of LILRB1 SNPs with HCMV disease is that it may be useful as part of a collection of biomarkers used to determine the relative risk for patients after receiving a transplant and to guide prophylactic use of antivirals in these patients. Many studies have investigated genetic influences on the immune response to HCMV; the genes implicated in modulating the control of HCMV after transplantation include IL-28B, CCL8, several microRNA, CLTA4, TLR9, DC-SIGN, and, most relevant to NK cells, NKG2C and KIRs (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). Further studies with additional cohorts could be useful to pinpoint the SNPs with the best correlation and to explore the relationship to the sequence of UL18 within each patient.…”
Section: Genotyping Of Transplant Patientsmentioning
confidence: 99%
“…There are two single nucleotide polymorphisms in the first exon of the TGF-β1 gene which increase the expression of the gene: +869T>C and +915G>C. In vitro studies showed that the genetic polymorphisms of TGF-β1 codon 10 T>C and codon 25 C>G result in increased production of this cytokine. The highest expression was observed in TT homozygous for TGF-β1 codon 10 T>C and GG genotype for TGF-β1 codon 25 C>G 23 . In addition, numerous studies demonstrated an association of the TGF-β1 gene with chronic renal transplant rejection and CsA toxicity 24 26 .…”
Section: Discussionmentioning
confidence: 90%
“…Various studies found that rs733618 SNP significantly correlated with many immune diseases. Niknam et al [ 21 ] demonstrated that -1722C allele negatively associated with acute rejection in kidney transplant patients with active Cytomegalovirus infection. A potential of rs733618 SNP also has been discovered in autoimmune myasthenia gravis.…”
Section: Discussionmentioning
confidence: 99%